The Role of Islamic Religious Education in Forming the Religious Character of Students - Susi Susilawati; Devi Aprilianti; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Islamic Religious Education is a subject that is considered effective in shaping the character of students, specifically religious character. Where this religious character has a big influence on the lives of students both in the world and in the hereafter. The results showed that Islamic religious education has an important role in character building, more specifically, the religious character which is rooted in the learning of faith.